Impact of Prolonged Exposure to Video Display Terminals on Macular Pigment Optical Density in Young Adult Filipinos - Ronald Y. Tiu, MD; Eleonore B. Iguban, MD (Philippine Journal of Ophthalmology)
Objective: This study assessed the correlation of macular pigment optical density (MPOD) and varying levels of exposure to video display terminals (VDT) among young adult Filipinos.